Effect of oxygen availability on the corrosion rate of reinforced concrete in marine exposure zones: inference from site and lab studies - Moore, Amy (Department of Civil Engineering, 2020)
Corrosion of steel in reinforced concrete structures is a large problem facing engineers today. The marine environment is considered to be the most severe owing to the high levels of chlorides available, and so structures located here are particularly vulnerable to chloride attack and chloride induced corrosion of steel. In order to intervene and address the concern of premature deterioration in the marine environment, design guidelines and frameworks have been developed and implemented. For example, the Eurocode (EN 206, 2013) provides three class designations in order to predict the severity of potential steel corrosion. The three exposure zones, namely i) structures exposed to airborne salts but not in direct contact with sea water, ii) submerged structures, and iii) structures in the tidal, splash and spray zones are given here in order of increasing assumed probability of corrosion. However, it has been found through condition assessments of structures along the Atlantic Ocean and Indian Ocean coasts of Southern Africa that structures in the tidal zone generally show no signs of corrosion damage despite having high levels of chlorides at the depth of reinforcement. Often, on a structure where both zones have the same cover to reinforcing, the splash and spray zone will show significant damage while the tidal zone shows no signs of reinforcement corrosion. These findings challenge the existing idea that the tidal zone can be characterised as the most severe exposure zone. In order to further understand the mechanisms of reinforcement corrosion within different marine environmental conditions, a total of 36 corrosion cells were manufactured with dimensions of 120 × 122 × 380 mm and placed in simulated marine environmental conditions. These three environmental conditions included submerged, cyclic wetting and drying, and periodic splashing. In order to simulate the submerged environment, the cover surface of the specimens were permanently saturated with a 5% NaCl solution while for the splash zone concrete specimens were sprayed with 5% NaCl solution every second day. The tidal zone attempted to simulate natural tidal conditions by exposing the corrosion cells to 12 hour cycles consisting of 6 hours wetting and 6 hours drying All 36 corrosion cells were connected to a data logger where the voltage was measured weekly across a resistor of 100Ω. Ohm’s law was then used to determine the current flowing through the circuit. The concrete cover depth was varied in the corrosion cells (10, 20 and 30 mm) as well as the w/b ratio (0,5 and 0,8). The corrosion current resulting from these corrosion cells were used to infer relationships between all 3 parameters (cover depth, w/b ratio, and exposure conditions) and their influence on the corrosion current. Three companion moisture specimens were cast per mix in order to establish moisture profiles in the different exposure zones. From these specimens, the relative humidity of the concrete at different cover depths and w/b ratio’s could be determined for corrosion cells located in differentexposure conditions. Companion cubes were also cast with the corrosion cells in order to determine the durability index values. The results of the experiments indicate that the exposure condition has a very large impact on the availability of oxygen, and hence the corrosion rate. High relative humidity (or moisture content) in concrete stifles the supply of oxygen to the steel, and hence prevents active corrosion. For concrete submerged and partially or completely saturated with water, oxygen accessibility can become limited at the steel surface. The results obtained conform to the widely accepted principle that submerged concrete is less vulnerable to corrosion as a result of insufficient oxygen supply at the reinforcing steel. For concrete exposed to a 6 hour cycle of wetting and drying, the corrosion rate was significantly lower at higher cover depths due to the short cycle durations, the pores surrounding the steel were still partially or fully saturated with water. As a result, oxygen diffused slower through the cover layer. Consequently, where the concrete in the tidal zone has drying times of about 6 hours and a cover depth exceeding 30 mm, the steel will be deprived of oxygen, and corrosion will be stifled. This means that the concrete in the tidal zone would theoretically perform as if it were permanently submerged (provided sufficient cover depth exists). Specimens exposed to a splash environment performed as expected. A low moisture content showed that oxygen is able to diffuse through the pore system and facilitate corrosion in the specimens. This is owing to the pores around the steel not being saturated with moisture, and oxygen being readily available to participate in the cathodic reaction. In the case of these specimens, the electrical resistivity of the specimens was found to be the main limiting factor in controlling the corrosion rate (and not cathodic control as with tidal and submerged specimens). As a result, it is recommended that the current SANS exposure classification be broadened to include concrete exposed to cyclic wetting and drying (i.e. tidal zone exposure) a separate category, and not be classified as having the same severity as the splash zone. The application of these research findings is in infrastructure that is primarily exposed to only tidal and submerged marine conditions.